Loss Accounting Practices among Takjil Sellers Grounded in Local Cultural And Religious Values - Thalib, Mohamad Anwar; Jusuf, Febiola; Tariki, Cindri; Pinga, Rika Oktaviyani (AL-QARDH, 2023)
This study aims to formulate loss accounting practices by takjil sellers based on local cultural values. This research uses a qualitative method. This study uses an Islamic ethnomethodological approach with five data analysis stages: charity, knowledge, faith, revelation, and courtesy. The results of the study found two ways for takjil sellers to avoid losses: distributing the remaining takjil merchandise for free to neighbors and family and giving bonuses. This loss accounting practice is conditional on the value of sharing, among others. Within the Islamic culture of Gorontalo, elders commonly impart this principle using the expression "lumadu diila o'onto, bo wolu-woluwo," which signifies the presence of something unseen yet still existing. The meaning is that this expression teaches that in life, don't just chase what is visible but also look for something that is invisible but exists. The value of sharing among others is living with the spirit of seeking sustenance that God blesses. This research contributes to the existence of local wisdom value-based loss accounting practices. The conclusion from the findings of this research is that takjil sellers practice loss accounting, which is not limited to material (money) but is conditional on non-material values in the form of local wisdom and religiosity.